Estudo da durabilidade do concreto frente à degradação com ataque de sulfatos em Estações de Tratamento de Esgoto (ETE) - Bender, Samantha Fernanda (Universidade do Vale do Rio dos Sinos, 2025)
The recurrence time established in NBR 8681:2003 for the durability of concrete structures is 50 years. It is expected that concrete structures will not present problems or pathologies within this interval. In this research, the durability and degradation of concrete are addressed due to their relevance and the need for special care in aggressive environments such as Sewage Treatment Plants (ETEs), which have difficulties in developing treatments for concrete with pathologies resulting from sulfate attack. The objective of this study is to evaluate the durability of sewage treatment plants, carrying out inspections, diagnosing anomalies and reporting on their treatment. Within this context, for the analysis and methodology applied in this study, “on-site” inspections were carried out in ten ETEs and samples were collected in one ETE for the sewage and concrete inside the tank in which the tests were subsequently carried out followed The test out followed the produce of NBR 16937 – Aggressive Waters – Durability of Concrete Part 6 with the collection of sewage and the X-ray Fluorescence Test (FRX) to verify degradation with the presence of sulfate with the collection of a sample from the internal wall of a tank in ETE sewage. In addition to the samples collected, to determine the data analysis, it was necessary to carry out a comparison with other researched standards regarding the chemical characteristics of the ETE sewage. The result of the sewage sample collected in June 2024 was SO₄⁻² = 181.10 mg/l. And the result of the collection in October 2024 presented the value found for the study SO₄⁻² = 211.97 mg/l. Regarding the analysis, concrete samples, collected on the inner wall of the treatment tank, were analyzed through FRX, resulting in that the five samples are basically formed by two components, SiO2 = 41.517% and CaO = 10.712% at the depth point at 3.00 cm and alkaline earth metals 6.357% (MgO) during sample collection. It also presented at the point 3.00 centimeters a low concentration of metal oxides (Na2O and K2O) and aluminum (Al2O3). After analyzing the results, it was possible to verify the intensity of the concrete degradation action in ETE in the face of sulfate attack
Keywords: ETE; Durabilidade; Sulfato; Ataque; Amostras; Durability; Sulfate; Attack; Sample; ACCNPQ::Engenharias::Engenharia Civil